Effect of itraconazole, food, and ethnic origin on the pharmacokinetics of ivosidenib in healthy subjects - Dai, David; Yang, Hua; Nabhan, Salah; Liu, Hua; Hickman, Denice; Liu, Guowen; Zacher, Jeffrey; Vutikullird, Apinya; Prakash, Chandra; Agresta, Samuel; Bowden, Chris; Fan, Bin (European journal of clinical pharmacology, 2019)
Purpose To assess the effect of ethnicity, food, and itraconazole (strong CYP3A4 inhibitor) on the pharmacokinetics of ivosidenib after single oral doses in healthy subjects. Methods Three phase 1 open-label studies were performed. Study 1: Japanese and Caucasian subjects received single doses of 250, 500, or 1000 mg ivosidenib (NCT03071770). Part 1 of study 2 (a two-period crossover study): subjects received 500 mg ivosidenib after either an overnight fast or a high-fat meal. Subjects received 1000 mg ivosidenib after an overnight fast in the single period of part 2 (NCT02579707). Study 3: in period 1, subjects received 250 mg ivosidenib; then, in period 2, subjects received oral itraconazole (200 mg once daily) on days 1–18, plus 250 mg ivosidenib on day 5 (NCT02831972). Results Ivosidenib was well tolerated in all three studies. Study 1: pharmacokinetic profiles were generally comparable, although AUC and C max were slightly lower in Japanese subjects than in Caucasian subjects, by ~ 30 and 17%, respectively. Study 2: AUC increased by ~ 25% and C max by ~ 98%, when ivosidenib was administered with a high-fat meal compared with a fasted state. Study 3: co-administration of itraconazole increased ivosidenib AUC by 169% (90% CI 145–195) but had no effect on ivosidenib C max . Conclusions No ivosidenib dose adjustment is deemed necessary for Japanese subjects. High-fat meals should be avoided when ivosidenib is taken with food. When co-administered with strong CYP3A4 inhibitors, monitoring for QT interval prolongation (a previously defined adverse event of interest) is recommended and an ivosidenib dose interruption or reduction may be considered. ClinicalTrials.gov NCT03071770, NCT02579707, and NCT02831972.